British society, 1680-1880 : dynamism, containment, and change - Price, Richard, 1944- (Cambridge University Press, 1999)
A sustained, radical new interpretation of British history in the eighteenth and nineteenth centuries, by a senior social historian confronting and questioning dominant interpretations. Scholars and students will find much of interest in this elegantly written and lucidly organised study.
Keywords: Great Britain -- Economic conditions -- 18th century.; Great Britain -- Economic conditions -- 19th century.; Great Britain -- Social conditions -- 18th century.; Great Britain -- Social conditions -- 19th century.; Grande-Bretagne -- Conditions économiques -- 18e siècle.; Grande-Bretagne -- Conditions économiques -- 19e siècle.; Grande-Bretagne -- Conditions sociales -- 18e siècle.; Grande-Bretagne -- Conditions sociales -- 19e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Economic history; Social conditions; Great Britain; Großbritannien; Sociaal-economische geschiedenis.; 1700-1899; Electronic books.